2018
DOI: 10.1111/vop.12601
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated changes in the equine flash visual evoked potential

Abstract: The overall equine FVEP waveform was similar across the normal life-span of the horse in our cross-sectional study. We found that the visual system of the foal seems to be well developed already at birth. Furthermore, our results showed a decrease in amplitudes and increase in some peak times with increasing age. We recommend that age-matched controls should be used when evaluating foals and young horses in clinical practice, whereas horses over the age of three years can be compared to other adult horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…9 Another study, however, reported the performance of the flash-VEP in 28 horses under sedation. 22 The decision to use sedative drugs was probably due to the uncooperative nature of this species coupled with the fact that there is no need for fixation for the flash stimulus, unlike the need for fixation when using pattern stimulus.…”
Section: Resultsmentioning
confidence: 99%
“…9 Another study, however, reported the performance of the flash-VEP in 28 horses under sedation. 22 The decision to use sedative drugs was probably due to the uncooperative nature of this species coupled with the fact that there is no need for fixation for the flash stimulus, unlike the need for fixation when using pattern stimulus.…”
Section: Resultsmentioning
confidence: 99%
“…The FVEP waveform recorded in all 17 horses in this study consisted of a series of positive and negative wavelets (P1, N1, P2, N2a, P3, N2, P4 and P5), as previously reported [ 16 , 17 ]. However, some wavelets were only present in a limited number of recordings in all horses.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen healthy adult Standardbreds (3–19 years old, mean ± standard deviation (SD); 10 ± 5.7 years, 4 geldings, 2 stallions and 11 mares), without any signs of ocular, visual or neurological disease at physical and ophthalmic examination, including obstacle course testing, were included in the study. Horses 1–10 and 1–17 were also included in two previous studies [ 16 , 17 ]. The study was approved by the Regional Ethical Committee (Uppsala Djurförsöksetiska nämnd, Sweden, C254/10 and C39/12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations